Residents’ and Tourists’ Visual Perception of Historic Urban Public Spaces: Evidence from Eye-Tracking and Subjective Evaluation in Zhengding Ancient City, China - Baohui Deng; Bingnan Lu; Yang Gao; Qing Zhang; Yike Hu; Pengjun Wu (Buildings, 2026)
Historic urban public spaces simultaneously serve as settings for heritage representation and everyday urban life. However, it remains unclear whether residents and tourists allocate visual attention and evaluate the same historic urban public spaces differently. Taking Zhengding Ancient City, China, as a case study, this research integrates static panoramic image-viewing experiments, wearable eye-tracking, and subjective evaluation to investigate differences in visual attention and perceived attractiveness between residents and non-local tourists. Twenty-five representative public-space scenes were selected, and 32 residents and 32 tourists participated in the experiment. Areas of interest (AOIs) were classified into architecture-related AOIs and space-based AOIs. Total fixation duration and fixation count were recorded using Tobii Pro Glasses 3, and subjective evaluations of architecture-related attributes and everyday spatial attributes were collected using a five-point Likert scale. The results showed that residents allocated significantly greater visual attention to space-based AOIs than tourists, whereas tourists reported higher evaluation scores for architecture-related attributes. Conversely, residents assigned higher evaluation scores to everyday spatial attributes. No significant difference was observed in overall satisfaction, suggesting that the two groups differed mainly in the aspects of the historic environment that they evaluated more positively rather than in their overall evaluations. Overall, the findings demonstrate that residents and tourists showed different patterns of visual attention allocation and subjective evaluation when viewing the same static representations of historic urban public spaces. These findings provide empirical evidence for understanding differences in visual attention and subjective evaluation between different user groups and offer methodological support for integrating eye-tracking with subjective evaluation in research on historic urban public spaces.